THE IMPACT OF A TRAINING PROGRAM UTILIZING DIRECTED GROUP INTERACTIONS ON THE PHYSICAL FITNESS INDICATORS OF 6–7-YEAR-OLD FOOTBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2025)
The athletic development of young football players requires a comprehensive approach that includes the parallel development of various aspects of preparedness. Objective: To determine the effectiveness of a training program that utilizes directed group interactions and has a parallel impact on the physical and technical preparation of 6–7-year-old football players based on their physical fitness indicators. Methods: Theoretical analysis and synthesis of scientific and methodological literature, abstraction, historical method, comparison, pedagogical testing, and methods of mathematical statistics. The duration of the pedagogical experiment was one academic year for the Youth Sports School (from September 2024 to May 2025). The experimental factor was the targeted application of group interactions with an emphasis on the parallel impact on the physical and technical training of athletes. A total of 73 athletes at the initial training stage participated (n=34 – control group and n=39 – experimental group, ages 6–7, Ivano-Frankivsk, Ukraine). Results: Based on the analysis of physical fitness data and its dynamics throughout the pedagogical experiment, we established that the implemented methodological approach of directed group interactions with a parallel impact on the physical and technical preparedness of beginner football players aged 6–7 demonstrated more comprehensive physical development in athletes. This was evident in improved results across a greater number of tests (p≤0.05), with statistically significant improvements in most cases (p≤0.05), as well as effects not only on key physical attributes for football players (speed-strength qualities) but also on coordination and special endurance compared to the data from beginner football players in the control group. Conclusions: The proposed training content for 6–7-year-old football players, which incorporates group interactions aimed at parallel influence on physical and technical training, proved to be more effective due to its diverse and targeted impact on athletes’ fitness levels.
Keywords: testing; content; direction; changes; comparison; training system; initial preparation stage